Translating property : the Maxwell Land Grant and the conflict over land in the American West, 1840-1900 - Montoya, María E., 1964- (University of California Press, 2002)
Although Mexico lost its northern territories to the US in 1948 battles over property rights have remained intense. This text shows how contending groups reinterpret the meaning of property to uphold their conflicting claims to land.